Wpływ cech drzewostanu i siedliska na występowanie borecznika sosnowca Diprion pini L. oraz borecznika zielonożółtego Gilpinia virens (Klug) (Hymenoptera, Diprionidae) na wybranych obszarach północnej Polski - Gawęda, Piotr; Grodzki, Wojciech (Leśne Prace Badawcze, 2020)
Pine sawflies (Hymenoptera: Diprionidae) belong to the most common pests of Scots pine Pinus sylvestris L. in the area of the Regional Directorates of State Forests in Toruń and Gdańsk. The two most destructive species, Diprion pini L. in the area of Puszcza Bydgoska and Gilpinia virens (Klug) in Bory Tucholskie, were investigated in this study. Our main aim was to characterize the two species in the Bydgoszcz Forest District in RDSF in Toruń and Kaliska in RDSF in Gdańsk, respectively, based on data gathered during outbreaks between 1991 and 2011. For this purpose, a geometric database was created, containing information about the year of outbreak, number of larvae observed after tree felling as well as selected stand and site features including stand age and species composition, stocking index, canopy closure, site index, humidity and fertility. By analyzing the occurrence of both species in relation to stand and site features, we were able to determine their environmental requirements, which are quite different from one another. D. pini preferred older stands, with a stocking index between 0.8–0.9, growing on fresh and dry coniferous sites, while species composition (share of pine), canopy closure or site index did not have any influence on its abundance. G. virens preferred middle-aged pure pine stands, with relatively open canopies, on fresh coniferous sites and poorer soils. The stocking index did not affect its occurrence.